The Effectiveness of Animation Video Media on Learning Outcomes of Fiqih Lessons for Madrsah Ibtidaiyah Students in the New Normal Time - Alimni Alimni; Alfauzan Amin; Meri Lestari (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2021)
The purpose of this study is to see how animated video media affects student learning outcomes in memorizing the reading of the obligatory prayers in Fiqh subjects at MIN 2 Bengkulu. The type of research used is quantitative with an experimental approach. Based on the survey results, it can be concluded that there is effectiveness between the use of animated video media and without animated video media. This can be proven from the results of the